Comparison of extracellular vesicle isolation and storage methods using high-sensitivity flow cytometry - Deville, Sarah; Berckmans, Pascale; Van Hoof, Rebekka; Lambrichts, Ivo; Salvati, Anna; Nelissen, Inge (PloS one, 2021)
Extracellular vesicles (EVs) are of interest for a wide variety of biomedical applications. A major limitation for the clinical use of EVs is the lack of standardized methods for the fast and reproducible separation and subsequent detection of EV subpopulations from biofluids, as well as their storage. To advance this application area, fluorescence-based characterization technologies with single-EV resolution, such as high-sensitivity flow cytometry (HS-FCM), are powerful to allow assessment of EV fractionation methods and storage conditions. Furthermore, the use of HS-FCM and fluorescent labeling of EV subsets is expanding due to the potential of high-throughput, multiplex analysis, but requires further method development to enhance the reproducibility of measurements. In this study, we have applied HS-FCM measurements next to standard EV characterization techniques, including nanoparticle tracking analysis, to compare the yield and purity of EV fractions obtained from lipopolysaccharide-stimulated monocytic THP-1 cells by two EV isolation methods, differential centrifugation followed by ultracentrifugation and the exoEasy membrane affinity spin column purification. We observed differences in EV yield and purity. In addition, we have investigated the influence of EV storage at 4°C or -80°C for up to one month on the EV concentration and the stability of EV-associated fluorescent labels. The concentration of the in vitro cell derived EV fractions was shown to remain stable under the tested storage conditions, however, the fluorescence intensity of labeled EV stored at 4°C started to decline within one day.